DETERMINATION OF SILVER CITRATE IN DIETARY SUPPLEMENTS BY SORPTION-ATOMIC ABSORPTION SPECTROMETRY - Зайцева, Галина; Пушкарьова, Ярослава; Попенко, Анна (SWorldJournal, 2025)
Silver (Argentum) is a trace element with pronounced antimicrobial, antifungal, and regenerative properties, widely applied in medicine and pharmacy in ionic (Ag⁺) and colloidal forms. Recently, silver citrate has gained special attention as a dietary sup